Electrochemical Behaviour and Determination of Baicalin on Nano-Al2O3 Modified Carbon Paste Electrode - Shi, Gao-Feng; Liu, Hai-Xiao; Wang, Guo-Ying; Su, Jin-Mei; Miao, Jian; Shi, Zhe-Ru (Asian Journal of Chemistry, 2015)
In this paper, the electrochemical behaviour of baicalin on nano-Al2O3 modified carbon paste electrode (NA-CPE) was investigated and further used for determination of baicalin. The nano-Al2O3 modified carbon paste electrode showed strong electrocatalytic effects to the oxidation of baicalin. In phosphate buffer solution (PBS, pH 7; 0.2 M) a pair of well-defined cyclic voltammetric oxidation peaks of baicalin appeared with the oxidation peak located at 157 mV (Epc) and 600 mV (Epc) (vs. SCE). The oxidation peak current was increased about 27.5 times more than that on traditional carbon paste electrode. The oxidation peak currents of baicalin in such modified electrode increased linearly with the concentration of baicalin in the range from 1 × 10-7 to 1 × 10-5 mol L-1 with a detection limit of 8 × 10-9 mol L-1. The method was applied in the determination of baicalin in samples with satisfactory results and the spiked recoveries were in the range of 95-105 %. These results suggest that the proposed electrode can be used for sensitive, simple and rapid determination of baicalin.